Premorbid Body Mass Index and Risk of Amyotrophic Lateral Sclerosis - O’Reilly, Éilis J. (2012)
OBJECTIVE: To determine if Amyotrophic Lateral Sclerosis (ALS) risk varies according to body mass index (BMI) captured up to three decades earlier. METHODS: At baseline 537,968 women and 562,942 men in five ongoing cohorts reported height, current weight and weight at age 18/21. During 14-28 years of follow-up 1,153 participants developed ALS. Cohort-specific Cox proportional hazards models were used to estimate rates that were then pooled with random effects models. RESULTS: Lower BMI at baseline was associated with ALS; for each 5-unit increase in BMI, ALS rates were 21% lower (95%CI: 14% to 27%). Compared to individuals with healthy BMI, ALS rates were significantly lower among the overweight (RR=0.76 [95%CI: 0.62-0.93]) and obese (RR=0.73 [95%CI: 0.55-0.96]). Among never-smokers the association persisted: RR=0.75 (95%CI: 0.65-0.85) for each 5-unit increase. Excluding the first seven years of follow-up, the associations were materially unchanged suggesting that weight loss from undiagnosed disease does not fully explain the findings. Overall, 75% of men and women had a healthy BMI at age 18/21, 15% of men and 8% of women were overweight or obese; there was no association with ALS risk although power was limited. CONCLUSION: These findings support an association between lower premorbid BMI and ALS.